Trade Union Legitimacy and Legitimation Politics in Australia and New Zealand. Issue 3 (30th June 2021) - Wright, Chris F.; McLaughlin, Colm
Abstract : This article analyzes how engagement in legitimation politics in Australia and New Zealand has enabled unions to influence the industrial relations policy process. It demonstrates how enhanced moral legitimacy with the wider public positively impacts unions' pragmatic legitimacy with governing political parties. Drawing on Grant's insider–outsider typology, we show how enhanced legitimacy can increase unions' power resources as insider groups with center‐left and, to a lesser extent, center‐right governing parties, which can enable greater influence over industrial relations policy.